(untitled) (Materiali di Estetica. Terza serie, 2020)
This short essay is essentially a remembrance of Formaggio’s teaching at the beginning of his stay in Padua. The importance of his studies about a new philosophical Aesthetics, connecting Hegel’s ideas with the phenomenological research rising from Husserl’s “heroic idealism”, and, later on, with Hartmann and Simmel, constitutes a basic contribution to the European contemporary Philosophy.